Instruction to do beam rectification work as per WEB sketch (SK125) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding instruction to do beam rectification work as per WEB sketch (SK125) of BRAC University new campus project.